Analisis dan Implementasi Hukum Kontrak: Tantangan dan Penyelesaian Sengketa - Adhitya Junjun Juniar (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
Contract law serves as a fundamental pillar of the modern legal system, regulating relationships and interactions between parties involved in various economic and business transactions. A contract functions as a legal instrument that ensures certainty, fairness, and the protection of rights and obligations among the parties. This paper provides an in-depth analysis of the essential principles of contract law, such as the principles of freedom of contract, consensualism, good faith, and pacta sunt servanda, as well as their practical implementation within the Indonesian business context. Furthermore, this study discusses common challenges in the application of contract law, including unequal bargaining positions, contract breaches, and difficulties in law enforcement. The discussion also explores mechanisms for resolving contractual disputes, both through litigation and alternative dispute resolution methods such as mediation and arbitration. This research aims to provide a comprehensive understanding of how contract law functions not only as a binding legal framework but also as an instrument to promote equitable, transparent, and sustainable business relationships.